Phenomenology of the Squeezed Hadronic Correlations at RHIC Energies - Padula, Sandra S. [UNESP]; Dudek, Danuce M. [UNESP]; Socolowski, Otavio (Progress Theoretical Physics Publication Office, 2012)
We briefly review the basic theoretical results on bosonic back-to-back correlations (bBBC) and compare our predictions with the first experimental search for squeezed correlations of K+K- pairs, performed by PHENIX. The hadronic squeezed correlations are very sensitive to the functional form of the time emission distribution. The comparison is made for three different kaon time distributions. From such comparison we show that the outcome of the experimental search may still be inconclusive but it does not exclude the existence of squeezing effects on hadrons with in-medium modified masses already at RHIC energies.